Atypical modulation of hypothalamic activity by social context in ASD. (February 2015) - Chaminade, Thierry; Da Fonseca, David; Rosset, Delphine; Cheng, Gordon; Deruelle, Christine
Highlights: A popular social interaction game was used to investigate hypotheses about neurophysiological correlates of ASD. Hypothalamus activity was not modulated by social context in ASD. The absence of modulation was correlated by a cortical area involved in anthropomorphization. Results suggest atypical social motivation associated with hypothalamic secretions in ASD. Abstract: High-functioning individuals with Autism Spectrum Disorder (ASD) and age- and verbal IQ-matched controls (CTL) were fMRI scanned when playing "stone paper scissors". They believed they were playing against three different opponents: a Human, a Robot endowed with an artificial intelligence attempting to win the game, and a Computer running a random number generator. No differences between ASD and CTL reached significance in canonical mentalizing regions, in the medial prefrontal cortex and right temporoparietal junction. In contrast, activity in a cluster located in the left hypothalamus, attributed to the paraventricular hypothalamic nucleus (PHN), increased in the CTL, but not ASD, group when participants played against the human compared to the artificial agent. The left temporoparietal junction (lTPJ), that has been previously associated with anthropomorphization, influenced this PHN cluster activity differently between groups, with a significantly negative functional connectivity when CTL played against the robot and when ASD participants played against the human. Brain activity results are consistent with the hypothesis that hypothalamus-secreted neurohormones, including oxytocin, could support motivation for social interactions and be impaired in autism. Brain connectivity results suggest that cortical encoding of social context information, putatively related to anthropomorphism, has a reversed effect on hypothalamus activity in autism.